Unlocking the puzzle of authoritarian persistence in Belarus: The role of the EU and Russia - Veranika Shykhutsina (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2023)
With the help of the concept of linkage and leverage, this paper aims at exploring how the relative influence of international actors (namely the European Union (EU) and Russia) can explain the persistence of the authoritarian regime in Belarus. The findings suggest that in the background of the great power competition that has played out in Belarus, EU's efforts to expand different types of linkages have not resulted in their sufficient levels to create leverage capable of neutralizing a significant Russian influence. Apart from the absence of substantial linkages between Belarus and the EU, such factors as Russia being a "countervailing power" providing the Belarusian regime with all sorts of support needed to sustain the autocratic rule; the absence of EU membership perspective; and diverging geopolitical interests of the EU member states leading to the absence of a coherent policy in relation to Belarus also negatively affect the strength and effectiveness of EU's leverage.
Keywords: F51; F59; P27; 330; Authoritarian persistence; Belarus; Democratization; Linkage and Leverage; Social contract